Effects of Pioglitazone on Asymmetric Dimethylarginine and Components of the Metabolic Syndrome in Nondiabetic Patients (EPICAMP Study): A Double-Blind, Randomized Clinical Trial - Pedram Shokouh; Adel Joharimoghadam; Hamidreza Roohafza; Masoumeh Sadeghi; Allahyar Golabchi; Maryam Boshtam; Nizal Sarrafzadegan (PPAR Research)
The present trial aimed to investigate the effects of pioglitazone on the serum level of asymmetric dimethylarginine (ADMA), a marker of endothelial function, and some indices of inflammation and glucose and lipid metabolism in nondiabetic metabolic syndrome patients. 104 eligible participants (57% female; age between 20 and 70) were enrolled in a double-blind placebo-controlled trial and were randomized to receive either pioglitazone (uptitrated to 30 mg/day) or matching placebo for 24 weeks. Participants were clinically examined and a blood sample was obtained at baseline and at the end of the trial. Pioglitazone significantly improved C-reactive protein level irrespective of changes in insulin sensitivity. Compared with the placebo group, alanine and aspartate transaminases were decreased and high-density lipoprotein cholesterol was increased after treatment with pioglitazone. A considerably greater weight gain was also recorded in the intervention group. We failed to observe any significant changes in serum ADMA in either group and between groups with and without adjustment for age, sex, and components of the metabolic syndrome. In a nutshell, pioglitazone seems to have positive effects on lipid profile, liver transaminases, and systemic inflammation. However, its previously demonstrated endothelial function-improving properties do not seem to be mediated by ADMA.